Calreticulin promotes EGF-induced EMT in pancreatic cancer cells via Integrin/EGFR-ERK/MAPK signaling pathway - Sheng, Weiwei (Cell Death Dis, 2017)
Our previous study showed that Calreticulin (CRT) promoted the development of pancreatic cancer (PC) through ERK/MAPK pathway. We next investigate whether CRT promotes EGF-induced epithelial–mesenchymal transition (EMT) in PC via Integrin/EGFR-ERK/MAPK signaling, which has not been reported yet to our knowledge. EGF simultaneously induced EMT and activated Integrin/EGFR–ERK/MAPK signaling pathway in 3 PC cells. However, CRT silencing significantly inhibited EGF function, including inhibiting EGF-induced EMT-like cell morphology, EGF-enhanced cell invasion and migration, and EGF induced the decrease of E-cadherin, ZO-1, and β-catenin and the increase of the key proteins in Integrin/EGFR-ERK/MAPK signaling (pEGFR-tyr1173, Fibronectin, Integrinβ1, c-Myc and pERK). Conversely, CRT overexpression rescued the change of EMT-related proteins induced by EGF in CRT silencing PC cells. Additionally, CRT was co-stained with pEGFR1173 (with EGF), Fibronectin and Integrinβ1 by IF under confocal microscopy and was co-immunoprecipitated with Fibronectin, Integrinβ1 and c-Myc in both PC cells, all of which indicating a close interaction of CRT with Integrin/EGFR–ERK/MAPK signaling pathway in PC. In vivo, CRT silencing inhibited subcutaneous tumor growth and liver metastasis of pancreatic tumor. A positive relationship of CRT with Fibronectin, Integrinβ1, c-Myc and pERK and a negative association of CRT with E-cad was also observed in vivo and clinical samples. Meanwhile, overexpression of the above proteins was closely associated with multiple aggressive clinicopathological characteristics and the poor prognosis of PC patients. CRT promotes EGF-induced EMT in PC cells via Integrin/EGFR-ERK/MAPK signaling pathway, which would be a promising therapy target for PC.